The Effects of Procedural Justice, Distributive Justice, and Interactional Justice of Service Recovery on PT.TELKOM Fixed Line Customer Satisfaction. - Kusnadi, Annisa Aulani; Suryadi, Nanang (Jurnal Ilmiah Mahasiswa FEB, 2012)
The purpose of this study is to analyze the influence of procedural justice, distributive justice, and interactional justice of service recovery on customer satisfaction, either simultaneously or partially, and to find out the most dominant independent variable which influences consumer satisfaction. Data were gathered by means of survey from PT.TELKOM fixed line users who experienced a service failure and complains directly to the company. The results show  that procedural justice, distributive justice, and interactional justice effect simultaneously and partially to the satisfaction of the consumer,  the effect of distributive justice on customer satisfaction was stronger than procedural and interactional justice. Key words: procedural justice,  distributive  justice,  interactional  justice, customer satisfaction, fixed line